Meningococcal disease. Polysaccharide meningococcal vaccines. The historical aspects and the current state of vaccine development. Report 2 - M. V. Abramtseva; A. P. Tarasov; T. I. Nemirovskaya (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The present article describes clinical signs of meningococcal disease. It justifies the necessity of its vaccine prevention. The article provides with the historical data on the evolution of inoculants from corpuscular inactivated vaccines to modern chemical polyvalent vaccines. It provides a glimpse of the efficacy of the use of corpuscular vaccines and considers the corresponding implications. The historical overview includes the use of mono-, di-, tetravalent polysaccharide vaccines, and the discussion on the role of bactericidal antibodies in the formation of immunity against meningococcal disease. The article also describes the experience of using polysaccharide vaccines in various countries and in different age groups in randomized clinical trials. It provides with the data analysis about the effect of vaccination on the level of meningococcal carriage and the incidence of meningococcal disease. The WHO’s position on the use of polysaccharide meningococcal vaccines in routine practice are also provided. In the conclusion the article presents the prospects for further use of polysaccharide vaccines to control the spread of meningococcal disease.